(untitled) (DAPesquisa, 2021)
In addition to police action, other factors contribute to crime prevention, including design. The Crime Prevention through Environmental Design (CPTED) approach uses design to modify the offender’s perception of the opportunity and benefits of crime. The goal of the research was to identify in Parque do Confisco (Belo Horizonte, Minas Gerais, Brazil), based on CPTED, factors that would stimulate criminal practice, as well as to verify if it would be possible to eliminate these factors. To this end, bibliographic research and spatial observation in the field were carried out. The analysis was based on the three strategies of CPTED: natural access control, natural surveillance and territorial reinforcement, as well as the investigation considered some aspects of the 3D approach (Designation, Definition and Design), typical of CPTED. The results revealed that low visibility, depredation and poor maintenance are the main aspects that stimulate criminal practice in the area. It is possible to implement improvements, however, it is necessary to build integrated projects that consider both physical and behavioral dimensions.